In vivo tracking of the tropism of mesenchymal stem cells to malignant gliomas using reporter gene‐based MR imaging. Issue 5 (31st October 2017) - Cao, Minghui; Mao, Jiaji; Duan, Xiaohui; Lu, Liejing; Zhang, Fang; Lin, Bingling; Chen, Meiwei; Zheng, Chushan; Zhang, Xiang; Shen, Jun
Abstract : Mesenchymal stem cells (MSCs) have emerged as a promising cellular vehicle for gene therapy of malignant gliomas due to their property of tumor tropism. However, MSCs may show bidirectional and divergent effects on tumor growth. Therefore, a robust surveillance system with a capacity for noninvasive monitoring of the homing, distribution and fate of stem cells in vivo is highly desired for developing stem cell‐based gene therapies for tumors. In this study, we used ferritin gene‐based magnetic resonance imaging (MRI) to track the tumor tropism of MSCs in a rat orthotopic xenograft model of malignant glioma. MSCs were transduced with lentiviral vectors expressing ferritin heavy chain (FTH) and enhanced green fluorescent protein (eGFP). Intra‐arterial, intravenous and intertumoral injections of these FTH transgenic MSCs (FTH‐MSCs) were performed in rats bearing intracranial orthotopic C6 gliomas. The FTH‐MSCs were detected as hypointense signals on T2‐ and T2*‐weighted images on a 3.0 T clinical MRI. After intra‐arterial injection, 17% of FTH‐MSCs migrated toward the tumor and gradually diffused throughout the orthotopic glioma. This dynamic process could be tracked in vivo by MRI up to 10 days of follow‐up, as confirmed by histology. Moreover, the tumor tropism of MSCs showed no appreciable impact on the progression of the tumor. These results suggest that FTH reporter gene‐based MRI can be used to reliably track the tropism and fate of MSCs after their systemic transplantation in orthotopic gliomas. This real‐time in vivo tracking system will facilitate the future development of stem cell‐based therapies for malignant gliomas. Abstract : What's new? Mesenchymal stem cells (MSCs) are promising vehicles for the delivery of therapeutic agents to brain tumors, due in part to their tumor homing and migratory capabilities. Noninvasive tools to monitor their movement and fate in vivo, however, are needed. In this study, MSC migration toward gliomas and the effects of MSCs on glioma growth were tracked using a ferritin reporter gene‐based magnetic resonance imaging strategy. About 17% of MSCs were observed migrating and diffusing throughout orthotopic gliomas in rats following intra‐arterial delivery. MSC tropism had no obvious effects on tumor progression.